Tinjauan Konstitusi terhadap Sistem Jaminan Sosial Nasional dan Badan Penyelenggara Jaminan Sosial - Hennigusnia Hennigusnia; Ardhian Kurniawati (Jurnal Ketenagakerjaan, 2021)
The 1945 Constitution of the Republic of Indonesia as Indonesia’s Constitution firmly mandates the state to develop social security system but not firmly mentions particular social security system that must be chosen by the state. Now the social security system which is chosen by the government is The National Social Security System (SJSN). In order to administrate The National Social Security System the government had made The Social Security Administration Body (BPJS) to administrate social security programs which were administrated by The State Owned Enterprises (BUMN) before. The objective of the research is to know the suitability of The National Social Security System (SJSN) and The Social Security Administration Body (BPJS) with The 1945 Constitution of the Republic of Indonesia’s mandate in the social security field. This research used the normative law research method. The normative law research method is the research method that uses secondary law materials. The result of the research showed that The National Social Security System had covered all of the people and shall empower the inadequate and underprivileged in society in accordance with human dignity. The Social Security Administration Body (BPJS) is non-profit and special public legal entities which is established under the law. The conclusion of the research is that The National Social Security System (SJSN) and The Social Security Administration Body (BPJS) had been suitable with The 1945 Constitution of the Republic of Indonesia’s mandate in the social security field.